Fournier's Gangrene Associated with Local Cutaneous HPV Lesions in a Previously Healthy Girl - Maria Tsinti; Theophani Tsekoura; Evangelos Blevrakis; Ioannis Vlachakis; Amalia Tsilimigaki-Christaki (Case Reports in Pediatrics)
A case of an 11-year-old prepubertal girl with Fournier's gangrene is presented. The diagnosis was posed after the disease had progressed to the typical clinical picture of frank gangrene. A benign viral infection, common warts, possibly represents the initiating event of the development of this necrotizing soft tissue infection. The development of childhood Fournier's gangrene in association with viral infections has been reported in the past. An optimal outcome was achieved by aggressive antibiotic and surgical treatment despite the late diagnosis. In children, Fournier's gangrene develops in previously healthy individuals with benign diseases often representing the initiating events; thus, high index of suspicion is necessary for an early diagnosis that will lead to the optimal outcome.